Adolescent's body: subsidies for intervention (Research, Society and Development, 2020)
Objectives: To identify the most significant physical changes in the body during adolescence and meet the qualifications attributed to these changes. Methods: Descriptive study conducted with 1600 adolescents (882 female and 718 male) aged between 12 and 18 years. Results: There was obtained a total of 2882 features (1179 male and 1703 female characteristics). In relation to changes in the body, the most cited were those that are constructs of male and female sexual characteristics, which denoted significant transformation in interpersonal behavior, unveiled as feelings of satisfaction. Among the changes, the highlights were the breasts (14.5%), waist and hips (8.0%), the overall (7.9%) and genital development (7.8%). The ratings assigned to the bodily changes were classified into two groups guided by the satisfaction and dissatisfaction in relation to these aspects. Conclusion: These events caused estrangement when cited as dissatisfaction, demanding time to adapt. family problems resulting from all these changes were also highlighted.